Quality Attribute-Price Relationship: Modernization of the Sweet Cherry Sector in Poland - Florkowski, Wojciech; Łysiak, Grzegorz (Zeszyty Naukowe SGGW w Warszawie - Problemy Rolnictwa Światowego, 2015)
This study describes the development of sweet cherry production in Poland in the context of relationship between quality attributes and wholesale prices as well as modernization of orchards creating opportunities for increased exports. Global demand for sweet cherries increases because of their perceived unique health benefits, but the fruit must have the desired quality attributes. The link between quality attributes and prices is illustrated using the wholesale prices collected during the harvest season in years of limited and normal crop in Poland, respectively. Among the discussed varieties is ‘Cordia’ which dominates in the modern orchards. As the sweet cherry production declines in the region, with the introduction of modern production technology, the increasing yields and volume produced creates opportunities for increased exports also to countries outside the EU.